Poincaré Inequalities for Composition Operators with Lφ-Norm. (1st April 2014) - Fang, Ru
Abstract : We establish the Poincaré-type inequalities for the composition of the homotopy operator, exterior derivative operator, and the projection operator with L φ - norm applied to the nonhomogeneous A -harmonic equation in L φ ( Ω ) -averaging domains.